The design of an RIS-assisted FDMA wireless sensor network for sum throughput maximization - Ghasemi, Omid Abachian; Azghani, Masoumeh; Amirani, Mehdi Chehel (Computer networks (Amsterdam, Netherlands : 1999), 2025)
In this article, we consider a reconfigurable intelligent surface (RIS)-assisted wireless sensor network (WSN), where sensors transmit data to a fusion center (FC) via the frequency division multiple access (FDMA) protocol. This sensor network leverages the capabilities of a primary network equipped with an RIS during periods of primary network inactivity. Power and bandwidth allocation, along with RIS phase shifts, are optimized to maximize sum-throughput (the performance metric), subject to constraints on total power and minimum sensor throughput. This optimization enables higher sum-throughput without increasing total energy consumption or bandwidth requirements. The non-convex optimization problem is tackled using a block coordinate descent (BCD) technique. This technique decomposes the problem into the three subproblems: power allocation subproblem, which is a convex subproblem solved using the Lagrange Dual Method (LDM) and the Karush-Kuhn–Tucker (KKT) conditions; the bandwidth allocation subproblem, which, due to its convexity, is solved similarly; and finally, the RIS phase shift adjustment subproblem, which is solved using gradient ascent. The BCD algorithm iteratively optimizes these subproblems until convergence is achieved. Numerical results demonstrate the superiority of the proposed scheme over its counterparts across various simulation scenarios. For instance, the proposed method with a 100-element RIS can improve the sum-throughput by approximately 50% compared to a conventional FDMA system.